PENINGKATAN PENGETAHUAN SISWA SMP NEGERI 2 KAMPA TENTANG BAHAYA NARKOBA - Fathra Annis Nauli; Yovindra Satria Maulana; Sakkot Mariani; Rahmah Fuadi; Susan Fakhirah; Febbi Nugra Restita; Fera Andini; Faiza Samudra Rifai; Rahmat Putra An-Nur; Riski Amaliyah; Silvia Monica Putri (Nusantara Hasana Berdikari, 2022)
Narcotics (narcotics and illegal drugs) are substances or drugs (made from natural, synthetic, or semisynthetic materials) that can cause decreased consciousness, hallucinations, and arousal. The negative impact of using Narcotics in addition to causing health effects in the form of dependence, lowering the level of consciousness and even the risk of death from overdose. However, although there have been many appeals and socializations made by various parties, the level of circulation and use is increasing. Therefore, the KUKERTA students of Riau University Sungai Putih Village held a socialization about the dangers of drugs with the socialization participants being students of SMP Negeri 2 Kampa. Through this study, the researchers aimed to measure: 1) How much knowledge of SMP Negeri 2 Kampa students about the dangers of drugs; 2) The effect of socializing the dangers of drugs on the knowledge of SMP Negeri 2 Kampa students about the dangers of drugs. The results of this study are: 1) Knowledge of SMP Negeri 2 Kampa students about the dangers of drugs tends to be good; 2) The attitude of SMP Negeri 2 Kampa students about the dangers of drugs strongly supports that drugs are harmful to physical and mental health and are dangerous for the survival of the younger generation. So it must be guarded by every element of society so that the younger generation does not fall into the dangers of drugs and protect the students of SMP Negeri 2 Kampa, especially those who are still in their infancy.